MAPPING RAILWAY LEVEL CROSSING ACCIDENT PATTERNS IN DAOP 8 OF EAST JAVA PROVINCE - Wicaksono, Achmad; Lasmini Ambarwati; Ita Suhermin Ingsih (Journal Innovation of Civil Engineering (JICE), 2024)
Railway-level crossing safety is a major issue in the transport system, especially in East Java where accidents occur frequently. This study aims to find the trend of accidents at the level crossing of DAOP 8 East Java and create data-driven preventive measures. The study used a mixed method approach, agent-based simulation, questionnaires, and interviews in addition to analyzing historical accident data. The results showed a significant prevalence of crashes in metropolitan locations, with higher risks during peak hours and homecoming periods. The largest incidences were reported in Sidoarjo and Surabaya, with significantly increased risk at night. The significant contributing factors are the presence of large vehicles, obstacles, weather, occurrence at night, and the presence of a crossbar. Keywords: Data-based prevention; DAOP 8 East Java Province; Level crossings; Risk analysis; Train accidents.